Luteal phase support for documented failure of placental steroidogenesis: A case report - Bryan Kratz, MD; Amer Rasheed; John P. Holden, MD (Elsevier, 2017)
Objective: To report a case of a habitual aborter that had a pregnancy reach near term and successfully delivered a viable female infant. Design: Report of a unique case of a G10P1 that was successfully able to maintain a pregnancy by maintaining serum levels of estradiol and progesterone at or above 200 pg/dL and 25 ng/dL respectively. This case provides a benchmark for exogenous support of estradiol and progesterone throughout pregnancy. Setting: A private advanced reproductive center. Patient: 39-year-old G10P1091 diagnosed to have antiphospholipid syndrome but continued to have continuous miscarriages despite accepted treatment. In addition, 8 products of conception were sent for cytogenetic testing and all were found to be normal. Interventions: Examination, laboratory studies, imaging, clinical judgment, and knowledge of previous treatment failures were used to guide the treatment of this patient. Fertility was achieved with continuous supplementation of progesterone, estrogen, LMW-heparin, and prednisone. Main Outcome Measure: Delivery of viable infant. Results: This advanced reproductive age woman had three subsequent pregnancies. While compliant with our prescribed protocol, the patient successfully carried two pregnancies to viability. Conclusion: Clinicians should be alert to the possibility of a luteal phase defect when a patient presents with recurrent fertility problems and multiple spontaneous abortions.